1998
DOI: 10.1007/s11661-998-0241-8
|View full text |Cite
|
Sign up to set email alerts
|

A transmission electron microscopy study of constituent-particle-induced corrosion in 7075-T6 and 2024-T3 aluminum alloys

Abstract: To better understand particle-induced pitting corrosion in aluminum alloys, thin foil specimens of 7075-T6 and 2024-T3 aluminum alloys, with identified constituent particles, were immersed in aerated 0.5M NaCl solution and then examined by transmission electron microscopy (TEM). The results clearly showed matrix dissolution around the iron-and manganese-containing particles (such as Al 23 CuFe 4 ), as well as the Al 2 Cu particles. While Al 2 CuMg particles tended to dissolve relative to the matrix, limited lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
128
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(145 citation statements)
references
References 13 publications
6
128
0
4
Order By: Relevance
“…So there is an assumption that a particular composition has a specific crystallographic structure which may not be valid. For example, Wei and coworkers (Gao, Feng et al 1998;Wei, Liao et al 1998) used TEM to study IM particles in AA2024-T3 and AA7075-T6 and found that compositions containing Al, Cu, Fe, Mn and Si, had a rhomohedral structure which did not match the hexagonal structure previously reported for particles of this type for example Al 8 Fe 2 Si or Al 10 Mn 3 Si. Classifying IM particles by shape is used both in metallurgy and corrosion.…”
Section: Aa2xxxmentioning
confidence: 92%
See 1 more Smart Citation
“…So there is an assumption that a particular composition has a specific crystallographic structure which may not be valid. For example, Wei and coworkers (Gao, Feng et al 1998;Wei, Liao et al 1998) used TEM to study IM particles in AA2024-T3 and AA7075-T6 and found that compositions containing Al, Cu, Fe, Mn and Si, had a rhomohedral structure which did not match the hexagonal structure previously reported for particles of this type for example Al 8 Fe 2 Si or Al 10 Mn 3 Si. Classifying IM particles by shape is used both in metallurgy and corrosion.…”
Section: Aa2xxxmentioning
confidence: 92%
“…Because these particles are rich in alloying elements, their electrochemical behaviour can be significantly different to the surrounding matrix phase. In most alloys pitting is associated with specific constituent particles present in the alloy (Buchheit 1995;Liao, Olive et al 1998;Wei, Liao et al 1998;Guillaumin and Mankowski 1999;Park, Paik et al 1999;Boag, Taylor et al 2010. These are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well known that the corrosion behavior of aluminum alloys can be significantly affected by the presence of second phase particles in the matrix. Particles that contain Al, Cu and Mg tend to be anodic relative to the alloy matrix, while those that contain Al, Cu, Fe and Mn tend to be cathodic relative to the matrix [5][6]. 6xxx series of Al-alloys are generally considered to be corrosion resistant although they can be susceptible to intergranular corrosion (IGC), which is supposed to be caused by Si concentration in excess of the Mg 2 Si ratio, precipitation of elemental Si or Cu-containing phases [7], or due to the anodic dissolution of the Mg 2 Si particles along grain boundaries [8].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 From a microstructural viewpoint, initiation of localized pitting corrosion is often associated with coarse cathodic intermetallic particles (IMPs), such as Al 7 Cu 2 Fe, Al 3 Fe, Al 2 Cu, and Al 2 CuMg, which are common in 2xxx and 7xxx series Al alloys. [4][5][6][7][8][9] A number of studies have been performed on electrochemical characteristics of these particles. 4,8,9 In general, they act as local cathodes and sustain oxygen reduction at a high rate to drive the pitting corrosion attack at the particle-matrix interface.…”
mentioning
confidence: 99%
“…7,[13][14][15] Andreatta and coworkers 7,14,15 investigated the galvanic coupling between the IMPs and the surrounding matrix phase of AA7075 in the as-quenched, peakaged T6 and over-aged T73 tempers using a micro-capillary cell and scanning Kelvin probe force microscopy (SKPFM). They suggested that the breakdown potential of areas containing the IMPs (Al 7 Cu 2 Fe and (Al,Cu) 6 (Fe,Cu) particles) was associated with the Volta potential difference between the IMPs and the matrix. The as-quenched and over-aged samples had larger Volta potential differences than the peak-aged sample.…”
mentioning
confidence: 99%